Forms of Blended Bicultural Identity: Identity Conflict and Harmony in Culturally Diverse Mauritius - van der Werf, F.M.; Verkuyten, Maykel; Martinovic, B.; Ng Tseung-Wong, Caroline (SAGE Publications Inc., 2020)
This study used a person-centered approach to distinguish groups of bicultural (national and ethnocultural) individuals in culturally diverse Mauritius. We focused on experiences of harmony or conflict among blended bicultural individuals and used representative data from the three numerically largest ethnocultural groups (Hindus, Creoles, and Muslims; Ntotal = 1,768). Cluster analyses indicated three groups of individuals with different identity profiles: conflicted blends (50%), harmonious blends (41%), and low blends (9%). Conflicted compared with harmonious blends were more concerned about keeping their ethnic group distinct and about the societal recognition of cultural diversity. In addition, higher social distance vis-à-vis outgroups was found among conflicted blends compared with harmonious blends. The findings for the three identity profiles are discussed in relation to existing theories on bicultural identity, Mauritius’ approach to ethnocultural diversity, and the country’s three main ethnocultural groups.
Keywords: bicultural identity; identity conflict; ethno-cultural identity; national identity; cultural diversity; Mauritius